GMP Conference 2022: Good Manufacturing Practices Methods Unity - article Editorial (Разработка и регистрация лекарственных средств)
On September 7–8, the VII GMP Conference with international participation will be held in Irkutsk. The organizers of the conference are the Ministry of Industry and Trade, the Federal State Institution «State Institute of Drugs and Good Practices». The operator is S-Group communication center.